THE STUDY OF LEGAL TERMINOLOGY SYSTEM IN FOREIGN LINGUISTICS (FORENSIC LINGUISTICS) - Feruza Mukhammadjon kizi Vahidova (Journals Park Publishing, 2024)
In the article, the issue of studying the system of legal terminology in foreign linguistics is systematically analyzed with the help of scientific and foreign literature on the example of forensic linguistics.
Keywords: foreign linguistics, legal terminology, system, forensic linguistics, terminology, concept, science, technique.